New insight into the role of fibroblasts in the epithelial immune microenvironment in the single-cell era - Wang, Liangzhe; Wang, Bo; Kou, Erwen; Du, Lin; Zhu, Yuanjie (Frontiers in Immunology, 2023)
The skin is exposed to environmental challenges and contains heterogeneous cell populations such as epithelial cells, stromal cells, and skin-resident immune cells. As the most abundant type of stromal cells, fibroblasts have been historically considered silent observers in the immune responses of the cutaneous epithelial immune microenvironment (EIME), with little research conducted on their heterogeneity and immune-related functions. Single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST) have overcome the limitations of bulk RNA sequencing and help recognize the functional and spatial heterogeneity of fibroblasts, as well as their crosstalk with other types of cells in the cutaneous EIME. Recently, emerging single-cell sequencing data have demonstrated that fibroblasts notably participate in the immune responses of the EIME and impact the initiation and progression of inflammatory skin diseases. Here, we summarize the latest advances in the role of fibroblasts in the cutaneous EIME of inflammatory skin diseases and discuss the distinct functions and molecular mechanisms of activated fibroblasts in fibrotic skin diseases and non-fibrotic inflammatory skin diseases. This review help unveil the multiple roles of fibroblasts in the cutaneous EIME and offer new promising therapeutic strategies for the management of inflammatory skin diseases by targeting fibroblasts or the fibroblastcentered EIME.